2016
DOI: 10.1186/s12944-016-0356-7
|View full text |Cite
|
Sign up to set email alerts
|

Associations of proteins relevant to MAPK signaling pathway (p38MAPK-1,HIF-1 and HO-1) with coronary lesion characteristics and prognosis of peri-menopausal women

Abstract: BackgroundThe present study was intended to explore whether three proteins within MAPK signaling pathway (i.e. p38MAPK-1, HIF-1 and HO-1) were correlated with peri-menopausal women’s coronary lesion features and prognosis.MethodsAltogether 1449 peri-menopausal women were divided into non-coronary artery disease (CAD) group (n = 860) and CAD group (n = 589), including 167 pre-menopausal CAD populations and 422 post-menopausal CAD populations. General information about CAD risk parameters were gathered, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Participants were included in the CAD group if ≥1 of their arteries had >50%‐diameter stenosis . Lesions of CAD patients were classified as single‐, double‐, and triple‐vessel lesions based on the amount of stenosed coronary vessel.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Participants were included in the CAD group if ≥1 of their arteries had >50%‐diameter stenosis . Lesions of CAD patients were classified as single‐, double‐, and triple‐vessel lesions based on the amount of stenosed coronary vessel.…”
Section: Methodsmentioning
confidence: 99%
“…The Gensini score was used to evaluate the degree of coronary artery stenosis . Specifically, the scoring was applied as follows: (1) score of 1 when the proportion of stenosis was ≤25%; (2) score of 2 when the proportion of stenosis was 25% to 50%; (3) score of 4 when the proportion of stenosis was 50% to 75%; (4) score of 8 when the proportion of stenosis was 75% to 90%; (5) score of 16 when the proportion of stenosis was 90% to 99%; and (6) score of 32 when the proportion of stenosis was 100%.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypoxia not only induces the expression of HIF-1α, but also increases the phosphorylation and activation of p38 MAPK in cancer cells (51). The activation of p38 MAPK signaling is necessary for HIF-1α accumulation and nuclear translocation (52). In the present study, we observed that the knockdown and overexpression of PKD1 elevated the expression of p-p38 MAPK in order to further ascertain whether p-p38 MAPK is involved in the regulation of PKD1 in hypoxia.…”
Section: Discussionmentioning
confidence: 58%